Green Maqashid: Reconstructing the Purpose of Islamic Law to Face the Global Ecological Crisis - Nasrullah , Aimar Comandini; Fikri, Hanif Muhammad; Alfindo, George Herdian; Yusdani, Yusdani (Unisia, 2025)
This article addresses the escalating global ecological crisis by reexamining the relevance of Islamic law through the lens of Green Maqashid, aiming to reconstruct the purposes of Islamic law so they respond adequately to contemporary environmental challenges. It seeks to demonstrate that the objectives of Islamic law (maqashid al-shari‘ah) possess an inherent ecological dimension that has not been systematically articulated within classical formulations. The study employs a qualitative, normative-conceptual methodology based on critical textual analysis of classical and contemporary maqashid scholarship, combined with an interdisciplinary engagement with Islamic environmental ethics and sustainability discourse. Drawing on modern maqashid theory, particularly systems-oriented and value-based approaches, the article develops the concept of Green Maqashid as an integrative framework. The main findings show that environmental protection can be coherently embedded within the structure of maqashid al-shari‘ah by reinterpreting its core objectives in relation to ecological balance, intergenerational justice, and public welfare. Green Maqashid reframes the protection of religion, life, intellect, progeny, and wealth through an ecological perspective, while also emphasizing environmental preservation as a foundational concern of Islamic law. The discussion highlights how this framework aligns Islamic normative principles with global sustainability agendas and provides ethical guidance for public policy, economic instruments, and community-based environmental initiatives. The article concludes that Green Maqashid offers a robust conceptual contribution to Islamic legal theory by expanding its moral horizon and practical relevance, with significant implications for developing environmentally responsible governance, sustainable economic practices, and faith-based ecological engagement.